2006
DOI: 10.1073/pnas.0510691103
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mediated by the dopamine D2 receptor potentiates circadian regulation by CLOCK:BMAL1

Abstract: Environmental cues modulate a variety of intracellular pathways whose signaling is integrated by the molecular mechanism that constitutes the circadian clock. Although the essential gears of the circadian machinery have been elucidated, very little is known about the signaling systems regulating it. Here, we report that signaling mediated by the dopamine D2 receptor (D2R) enhances the transcriptional capacity of the CLOCK:BMAL1 complex. This effect involves the mitogen-activated protein kinase transduction cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
135
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 75 publications
1
135
0
2
Order By: Relevance
“…Suppression of DA decreases PER2 levels in the dorsal striatum of rats (Hood et al, 2010). Conversely, activation of D1 or D2 receptors increases Per1 transcription in striatum and retina (Imbesi et al, 2009;Yujnovsky et al, 2006). Notably, Per1 overexpression leads to longer circadian periods (Numano et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of DA decreases PER2 levels in the dorsal striatum of rats (Hood et al, 2010). Conversely, activation of D1 or D2 receptors increases Per1 transcription in striatum and retina (Imbesi et al, 2009;Yujnovsky et al, 2006). Notably, Per1 overexpression leads to longer circadian periods (Numano et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, timed treatment with a D1 DA receptor agonist shifts circadian phase of fetal hamsters (Viswanathan and Davis, 1997;Viswanathan et al, 1994), possibly due to activation of D1 receptors in the mammalian SCN (Rivkees and Lachowicz, 1997;Weiner et al, 1991). DA also regulates core clock components in retina and striatum (Hood et al, 2010;Imbesi et al, 2009;Yujnovsky et al, 2006). Thus, DA may be crucially involved in both manic behavior and disrupted circadian rhythms in BD.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 A risk allele that interacts with en2 variants to perturb the normal spatial/temporal expression of en2 could alter normal brain development, a point that has resonance with per1's role in the cell division cycle 128 and dopamine D2 receptor-mediated signaling. 129 The timing, contextual/memory deficits and other implications suggested by the association of per1 and npas2 with autistic disorder may manifest concurrently and/or developmentally, for example, through infant-adult interaction that is timingdependent. [130][131][132][133] Neonatal physiological oscillations (sleep-wake cyclicity and cardiac vagal tone) predict mother-infant synchrony at 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Imbesi et al found that D2 receptor agonists inhibited the expression of Clock and Per1 genes, while D1 receptor agonists enhanced the expression of Per1, Clock, NPAS2 and Bmal1 [7]. Besides, Yujnovsky et al found a drastic decrease of Per1 gene transcription in the retinas of D2R (dopamin D2 receptor)-null mice [8]. Dopamine also resets the rhythm during the prenatal stage in the circadian pacemaker SCN [10,11].…”
mentioning
confidence: 80%
“…To be specific, dopamine can upregulate the transcriptional activity of Clock/Bmal complex through enhancing the recruitment and phosphorylation of the transcriptional coactivator cAMP-responsive element-binding proteins [8].…”
mentioning
confidence: 99%